Strategic Human Resource Management and Organizational Performance in Emerging Markets - Agus Rohmat Hidayat (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This study examines the relationship between strategic human resource management (SHRM) practices and organizational performance in emerging markets. Drawing on data from 450 organizations across Indonesia, Malaysia, Thailand, Vietnam, and the Philippines, we investigate how SHRM practices influence organizational outcomes through mediating mechanisms of innovation capabilities and organizational resilience. Using structural equation modeling (SEM), our findings reveal that SHRM practices significantly predict organizational performance (? = 0.68, p < 0.001), with innovation capabilities and resilience serving as key mediators. The study contributes to the SHRM literature by demonstrating that context-specific implementation of HR practices in emerging markets requires adaptation to local institutional environments, cultural norms, and workforce characteristics. Practical implications suggest that organizations operating in emerging markets should prioritize developing agile HR systems that balance global best practices with local responsiveness